2018
DOI: 10.1247/csf.18008
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles Rescue H<sub>2</sub>O<sub>2</sub>-induced Inhibition of Cardiac Differentiation

Abstract: The anti-oxidative property of mesoporous silica nanoparticles (MSNs) has been proposed previously, which prompted us to investigate the potential protective effect of MSNs on human embryonic stem cells (hESCs) against oxidative stress. To this purpose, the cell viability was determined by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide assay. Apoptosis was analyzed by Annexin V/propidium iodide double-staining method. The intracellular glutathione, superoxide dismutase and malondialdehyde we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…12 There are few published studies demonstrating effects of any NPs on cardiomyocytes. In addition to cytotoxicity, reduced contraction amplitudes (with TiO 2 -NPs 13 ), enhanced beating properties (with mesoporous SiO 2 -NPs 14 ), interference with ion channels (with Pt-NPs 15 ), and increased Ca 2þ spikes and local Ca 2þ flux (chitosan NPs 16 ) have been reported. The 2016 overview devoted specially to NPs that cardiotoxicity considers such NP species as zinc, titanium, silver, carbon, silica, and iron oxide but does not mention lead or cadmium in any chemical form.…”
Section: Introductionmentioning
confidence: 99%
“…12 There are few published studies demonstrating effects of any NPs on cardiomyocytes. In addition to cytotoxicity, reduced contraction amplitudes (with TiO 2 -NPs 13 ), enhanced beating properties (with mesoporous SiO 2 -NPs 14 ), interference with ion channels (with Pt-NPs 15 ), and increased Ca 2þ spikes and local Ca 2þ flux (chitosan NPs 16 ) have been reported. The 2016 overview devoted specially to NPs that cardiotoxicity considers such NP species as zinc, titanium, silver, carbon, silica, and iron oxide but does not mention lead or cadmium in any chemical form.…”
Section: Introductionmentioning
confidence: 99%
“…MSNs are widely used in in vivo therapeutical applications, due to their improved biocompatibility, specificity, and low toxicity. Although MSNs have been shown to relieve H 2 O 2 ‐elicited intracellular oxidative stress in a cardiac model, [ 230 ] the exact mechanism of their action on neuronal models is yet to be investigated. With their exceptionally large surface area resulting from increased porosity, MSNs also provide a great platform for drug encapsulation and surface functionalization.…”
Section: Nanocarrier‐based Delivery Of Antioxidantsmentioning
confidence: 99%
“…Previous studies have shown that elevated ROS could reduce the proliferation and pluripotency of hPSCs [ 14 , 15 ]. Similarly, treatment with hydrogen peroxide (H 2 O 2 ) increased cellular ROS and impaired cardiac differentiation of hESC-derived embryoid bodies (EBs) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%